Let's make up a story: design and evaluation of an improvisational storytelling robot to foster older adults' meaning and purpose in life - Hsu, Long-Jing; Joshi, Swapna; Seliger, Erin; Amon, Kyrie Jig; Kamino, Waki; Randall, Natasha; Khoo, Weslie; Crandall, David J.; Agnihotri, Abhijeet; Tsui, Katherine M.; Šabanović, Selma (Frontiers in Dementia, 2025)
ObjectiveImprovisational storytelling can encourage older adults to reflect on their meaning and purpose in life by creatively bringing up valuable patterns and themes from their memories and experiences. Robots for storytelling with older adults have so far aimed to boost their cognitive function and social interactions, rather than a pursuit of meaning and personal reflection.MethodsWe used empirical analysis of expert storytelling facilitators to design a Wizard-of-Oz (WoZ) operated robot that engages older adults in improvisational storytelling to tap into their meaning and purpose in life.ResultsOur analysis of stories created by 16 participants and their interactions with the robot suggests that older adults reflected on family, relationships, and activities meaningful to them and engaged with the robot as a companion during the activity.DiscussionWe provide design implications for an autonomous storytelling robot and discuss the potential for information collected during the storytelling activity to further foster exploration of meaning and purpose among older adults.